Identification of BAG5 as a Potential Biomarker for Parkinson’s Disease Patients With R492X PINK1 Mutation - Fu, Yu; Chen, Yongkang; Tian, Haiyan; Liu, Han; Qi, Dan; Wu, Erxi; Wang, Xuejing (Frontiers in Neuroscience, 2022)
Parkinson’s disease (PD) is a degenerative, progressive nervous system disorder with an unknown cause. PINK1 [phosphatase and tensin homolog deleted on chromosome 10 (PTEN)-induced putative kinase 1] causative mutations R492X may cause autosomal recessive early-onset parkinsonism. In this study, we utilized patient samples and cell line system to investigate roles of Bcl2-associated athanogene 5 (BAG5) in PD patients with R492X PINK1 mutation. We show that the expression levels of BAG5 in the skin tissues from PD patients with R492X PINK1 mutation are markedly lower than those from the healthy control subjects in a small cohort of patients, which has not been recognized before. In addition, we demonstrate that BAG5 physically binds to R492X mutated PINK1 protein. Furthermore, we reveal that BAG5 promotes the degradation of R492X mutated PINK1 protein via ubiquitin/proteasome-dependent pathway, suggesting that decreased level of BAG5 may lead to R492X mutated PINK1 protein accumulation. These findings suggest that BAG5 may serve as an early detection biomarker for PD patients with R492X PINK1 mutation and provide important new insights on how BAG5 affects R492X mutated PINK1 protein, highlighting therapeutic targets for this disease.